Perceptions of Thalassemia Patients Regarding the Arrangements of Medical Care during COVID-19 in Jordan - Alazzam, Abdelbaset; Al Refai , Safa'a (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims to explore the perceptions of Thalassemia patients towards the arrangements of medical care during the COVID-19 pandemic in Jordan. The study focuses on five areas: patient's rights, a healthy environment, doctor-patient relationship, patient privacy, and the interaction between medical staff and patients. Methods: The study was conducted on a purposive sample of 213 patients at Princess Rahma Hospital in Jordan, utilizing a descriptive analytical approach. Results: The results revealed several challenges faced by Thalassemia patients at the hospital. These include a shortage of blood units, extended waiting times for receiving necessary care, inadequate time allocated to each patient, fatigue and increased stress due to malfunctioning lifts, overcrowding of visitor patients in limited space, difficulty in contacting and meeting doctors, unavailability of required vaccinations, laboratory tests, and medications, and complex administrative procedures. The study also highlighted negative experiences related to the treatment and communication skills of medical staff. Conclusions: Based on the findings, the study recommends that the Thalassemia Foundation prioritize the well-being of its patients during the COVID-19 pandemic. This can be achieved by implementing health measures recommended by the World Health Organization and adopting the recommendations of the International Thalassemia Federation.